2021
DOI: 10.1021/acs.organomet.1c00315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precatalyst Oxidation State in C–N Cross-Couplings with 2-Phosphinoimidazole-Derived Bimetallic Pd(I) and Pd(II) Complexes

Abstract: We report the catalytic activity of two phosphinoimidazolederived bimetallic palladium complexes in Pd-catalyzed amination reactions. Our studies demonstrate that the starting oxidation state (Pd(I) or Pd(II)) of the dimeric complex has a significant effect on the efficiency of the catalytic reaction. The corresponding Pd(I) complex shows higher reactivity in Buchwald−Hartwig aminations, while the Pd(II) complex is much more reactive in carbonylative amination reactions. These new dimeric palladium complexes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…11 We also demonstrated that the oxidation state of the Pd dimer (Pd(I) vs Pd(II)) can have a dramatic impact on catalysis in Buchwal-Hartwig amination and aminocarbonylation reactions. 12 In an attempt to expand the applications of these ligands to bimetallic catalysis, we attempted the synthesis of the corresponding Rh complexes. When 2-phosphinoimidazole ligand 1 was reacted with [Rh(cod)Cl] 2 , monometallic complex 2 was formed (Figure 2a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 We also demonstrated that the oxidation state of the Pd dimer (Pd(I) vs Pd(II)) can have a dramatic impact on catalysis in Buchwal-Hartwig amination and aminocarbonylation reactions. 12 In an attempt to expand the applications of these ligands to bimetallic catalysis, we attempted the synthesis of the corresponding Rh complexes. When 2-phosphinoimidazole ligand 1 was reacted with [Rh(cod)Cl] 2 , monometallic complex 2 was formed (Figure 2a).…”
mentioning
confidence: 99%
“…These bimetallic complexes enable a new naphthalene synthesis reaction by accessing dimeric Pd­(III) intermediates in catalysis . We also demonstrated that the oxidation state of the Pd dimer (Pd­(I) vs Pd­(II)) can have a dramatic impact on catalysis in Buchwal-Hartwig amination and aminocarbonylation reactions . In an attempt to expand the applications of these ligands to bimetallic catalysis, we attempted the synthesis of the corresponding Rh complexes.…”
mentioning
confidence: 99%
“…We recently reported the synthesis of 2-phosphino­imid­azole-derived bimetallic Pd(I) and Pd(II) complexes and their exceptional reactivity in tandem ketone alpha-arylation annulation reactions for naphthalene synthesis . In an attempt to synthesize the corresponding Rh complexes, we reacted 2-phosphino­imid­azole ligand 1 with [Rh(cod)Cl] 2 and observed formation of monometallic complex 2 (Figure a).…”
mentioning
confidence: 99%